Ageing-Demographic Time-Bomb or Social Construct: Outline of the Potential Horizons and Opportunities - James Power John (Journal of Aging Research And Healthcare, 2016)
Ageing whilst an inevitable process in the human being, does not have to be marked by progressive decline and social withdrawal. `Ageism’ can generate a number of negative and at times destructive perspectives, labelling the elderly and possibly encouraging them to reflect the attitudes and behaviour of the label. This discussion paper addresses concerns about the `demographic time-bomb’ in some advanced economies from a sociological and policy perspective; exploring briefly functional, critical and social action theory. The paper concludes by suggesting that social perspective significantly translate to social behaviour and interaction with and by the elderly. Many of the ageist preconceptions are not necessarily supported by research, and that advancing age should be marked by empowerment, participation, choice and more effective social integration or reintegration. Importantly, the ageing process and perspectives on ageing need to be addressed, both politically and structurally within societies.
Keywords: ageing